FUNGSI-FUNGSI MANAJEMEN DALAM KEGIATAN EKSTRAKURIKULER PRAMUKA DI MADRASAH - Nurdiana, Mia; Prayoga, Ari (Perkumpulan Sarjana Manajemen Pendidikan Islam Indonesia, 2018)
The application of management functions in scout extracurricular activities in these three schools differs according to the policies of the madrasa head and the madrasa/school culture so that the output is different. This study aims to describe management functions in three madrasas/schools, starting from planning, organizing, actuating and controlling extracurricular. The research method used is qualitative. The results of the study indicate that (1) Planning includes activities to determine extracurricular goals, extracurricular goals, activities schedule and extracurricular coaches; (2) Organizing includes division of tasks, cooperation built with external parties and grouping of students; 3) Mobilization includes the implementation of extracurricular activities, participation of students and the assessment system of students; 4) Controlling is carried out with oral and written reporting.